2013
DOI: 10.3109/10717544.2013.856964
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of solubility, dissolution release profile and reduction in ulcerogenicity of piroxicam by inclusion complex with skimmed milk

Abstract: Context: Piroxicam (PXM), a non-steroidal anti-inflammatory drug which is poorly soluble in water and ulcerogenic. Milk has been used against the gastric disturbances caused by non-steroidal anti-inflammatory drugs. In this study, skimmed milk (SKM) is used as the carrier for inclusion complex (IC) due to its surface active agent and amino acid content. Purpose: To enhance the solubility, dissolution rate and prevent ulcerogenicity of PXM though IC with SKM. Methods: IC of PXM were prepared with SKM by solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The arbitrary scores (ASs) given to the ulcers were 0 for no ulcer/lesion, 0.5 for one or more ulcers of length <1 mm, 1 for ulcers/lesions of length 1–2 mm, and 2 for ulcers/lesions with length >2 mm. The arbitrary scores were multiplied with the number of lesions to determine the lesion index as follows [ 54 ]: Gastric lesion index (GLI) = AS × No. of ulcers/lesions …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The arbitrary scores (ASs) given to the ulcers were 0 for no ulcer/lesion, 0.5 for one or more ulcers of length <1 mm, 1 for ulcers/lesions of length 1–2 mm, and 2 for ulcers/lesions with length >2 mm. The arbitrary scores were multiplied with the number of lesions to determine the lesion index as follows [ 54 ]: Gastric lesion index (GLI) = AS × No. of ulcers/lesions …”
Section: Methodsmentioning
confidence: 99%
“…Microscopic Analysis All the stomachs of the animals were preserved in 20% v/v formalin buffer solution for histological analysis. Tissue sections of animals were observed under a microscope fitted with a 5 megapixel camera (Accuscope 3000, Commack, NY, USA) to determine the extent of ulceration and mucosal damage [54].…”
Section: Macroscopic Scoringmentioning
confidence: 99%
“…The dispersions were kept in gyratory shaker at 25 ºC for 24 hrs following which the samples were filtered through Whatman filter paper(No. 1), suitably diluted withcorresponding medium and absorbances were measured spectrophotometrically at 270 and 273 nm respectively for double distilled water and phosphate buffer (pH 6.8) [32][33][34][35]. Solubilities of the formulations and corresponding % solubility enhancement with respect to the pure drug were calculated from the respective calibration curves by using the following formula(Equation 1).…”
Section: Determination Of Equilibrium Solubilitymentioning
confidence: 99%
“…The fat content in mammalian milk comprises over 95% triglycerides [1]. The recognition that these milk lipids can offer a solubilising environment for poorly water-soluble lipophilic drugs has led to a range of studies focusing on the solubility of drugs in milk [[2], [3], [4], [5], [6]] and in a limited number of studies the effect of milk on in vivo absorption and bioavailability [[7], [8], [9]]. The solubility of drugs in milk has been reported to be enhanced compared to that in aqueous media without fat present and in limited in vivo studies consequent increases in systemic exposure have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%